Sports injuries in physical education teacher education students. Issue 4 (5th February 2013) - Goossens, L.; Verrelst, R.; Cardon, G.; De Clercq, D.
<x xml:space="preserve">Abstract</x> Sports injuries could be highly detrimental to the career of a physical education teacher education (PETE) student. To enable the development of future sports injury prevention programs, sports injuries in 128 first‐year academic bachelor PETE students were registered prospectively during one academic year. Common risk factors for sports injuries, taken from the literature, were also evaluated by means of logistic regression analysis. We found an incidence rate of 1.91 and an injury risk of 0.85, which is higher than generally found in a sports‐active population. Most injuries involved the lower extremities, were acute, newly occurring injuries, and took place in non‐contact situations. More than half of all injuries lead to an inactivity period of 1 week or more and over 80% of all injuries required medical attention. A major part of these injuries happened during the intracurricular sports classes. Few differences were seen between women and men. A history of injury was a significant risk factor (P = 0.018) for the occurrence of injuries, and performance of cooling‐down exercises was significantly related to a lower occurrence of ankle injuries (P = 0.031). These data can inform future programs for the prevention of sports injuries in PETE students.